Still more stories from Grandma's attic - Richardson, Arleta; Leder, Dora. (Elgin, IL : Chariot Books, 1980)
A collection of tales told by a grandmother about her childhood on a Michigan farm in the 1890's.
Keywords: Farm life -- Fiction; United States -- Social life and customs -- 1865-1918 -- Fiction